Analysis of the Preventive Medicine Undergraduate Curriculum in China: The West China School of Public Heath Experience: A Case Study - Zhao, Li; Wang, Ruiou; Xin, Junguo; Chen, Quan; Li, Chunyan; Holsinger, James W.; Ma, Xiao (Frontiers in Education, 2017)
In China, the preventive medicine undergraduate professional training program is the major approach to training public health practitioners. The history of undergraduate education in public health/preventive medicine in China is reviewed utilizing the example of the West China School of Public Health at Sichuan University as an example for analyzing this undergraduate major and its curriculum. Needed reforms in the Chinese undergraduate preventive medicine programs are presented including: review of the traditional preventive medicine course content, revision of its curriculum structure, the need to increase practical experience and to develop variety in teaching and assessment techniques, and systematic planning for curriculum reform. Current efforts at reform of the preventive medicine undergraduate program at Sichuan University’s West China School of Public Health are presented.